Continuous Dependence of Solutions to Functional Differential Equations on the Scaling Parameter - Rossovskii, Leonid Efimovich (Eurasian Mathematical Journal, 2016)
For a functional differential equation with rescaling, we establish the G̊arding-type inequality uniform with respect to the scaling parameter \( p \). This allows us to study the limit behaviour of solutions to the Dirichlet problem as \( p → 1 \).